Leave or Stay as a Risky Choice: Effects of Salary Reference Points and Anchors on Turnover Intention - Xiong, Guanxing; Wang, X. T.; Li, Aimei (Frontiers in Psychology, 2018)
Within a risky choice framework, we examine how multiple reference points and anchors regulate pay perception and turnover intentions in real organizational contexts with actual employees. We hypothesize that the salary range is psychologically demarcated by three reference points into four regions, the minimum requirement (MR), the status quo (SQ) and the goal (G). Three studies were conducted: Study 1 analyzed the relationship between turnover intention and the subjective likelihood of falling into each of four expected salary regions; Study 2 tested the mediating effect of pay satisfaction on salary reference point-dependent turnover intention; and Study 3 explored the anchoring effect of estimated peer salaries. The results show that turnover intention was higher in the region below MR or between MR and SQ but lower in the region above G or between SQ and G. That is, turnover intention can be high even in situations of salary raise, if the raise is below a salary goal (i.e., leaving for a lack of opportunity) and low even in situations of salary loss, if the expected salary is still above the MR (i.e., staying for security). In addition, turnover intention was regulated by pay satisfaction and peer salaries. In conclusion, turnover intention can be viewed as a risky choice adapted to salary reference points.